Magnetic Resonance Imaging of Cardiovascular Fibrosis and Inflammation: From Clinical Practice to Animal Studies and Back. (22nd August 2013) - Doltra, Adelina; Stawowy, Philipp; Dietrich, Thore; Schneeweis, Christopher; Fleck, Eckart; Kelle, Sebastian
Abstract : Late gadolinium enhancement is the technique of choice for detecting myocardial fibrosis. Although this technique is used in a wide range of cardiovascular pathologies, ischemic cardiomyopathy and the workup for myocarditis and other cardiomyopathies make up a significant proportion of the total indications. Multiple studies during the last decade have demonstrated its utility to adequately characterize myocardial tissue and offer diagnostic and prognostic information. Recent T1 mapping techniques aim to overcome the limitations of late gadolinium enhancement to assess diffuse fibrosis. 19 F magnetic resonance has recently emerged as a promising technique for the assessment of inflammation. In the following review we will discuss the basic aspects of fibrosis assessment with MR and its utility for diagnostic and prognostic evaluation. We will also address the topic of cardiovascular inflammation imaging with 19 F as a potential new development that may broaden the indications for MR in the future.